A novel chimeric endolysin Cly2v shows potential in treating streptococci-induced bovine mastitis and systemic infections - Wang, Shuang; Li, Xinxin; Ji, Junrou; Li, Xiangmin; Zhu, Hechao; Duan, Xiaochao; Hu, Dayue; Qian, Ping (Frontiers in Microbiology, 2024)
Streptococcus species are important pathogens implicated in bovine mastitis, causing considerable economic losses within the global dairy industry. With the development of multidrug-resistant bacteria, it is crucial to develop novel antibiotic alternatives. Here, we constructed a novel chimeric endolysin, Cly2v, which comprises the Ply2741 CHAP domain (1-155aa) and the PlyV12 CBD domain (244-309aa). Biochemical characterization analysis indicated that Cly2v exhibits a melting temperature of 50.7°C and retains stable bactericidal activity at pH=3-10. In vitro experiments demonstrated that Cly2v exhibited more efficient bactericidal activity against Streptococcus compared to the parental endolysin Ply2741. Cly2v (25μg/ml) can effectively inhibit and reduce biofilms formed by Streptococcus, resulting in a 68% and 44% reduction in OD590nm for S. agalactiae X2 and S. uberis 002-1 biofilms. Notably, in a mouse mastitis model, treatment with Cly2v (50μg/gland) led to a reduction in bacterial load by 2.16 log10CFU/ml and decreased inflammatory cytokine levels in mammary tissue. To our knowledge, this represents the first application of a chimeric endolysin in the treatment of early-stage mouse mastitis induced by streptococci. Additionally, in a systemic infection model, treatment with Cly2v 400μg/mouse) provided protection rates of up to 100% and 78% against S. agalactiae ATCC13813 infections when challenged for 1 h and 3 h, respectively. Furthermore, a significant reduction in bacterial loads was observed in the blood and organs compared to the PBS group. In summary, Cly2v possesses significant potential as an alternative antibiotic for the treatment of streptococci-induced bovine mastitis and systemic infections.